Single-level Cervical Arthroplasty with Prodisc-C Vivo Artificial Disc: Five-year Follow-up Results From One Center. Issue 2 (15th January 2022) - Cao, Shuo; Zhao, Yanbin; Sun, Yu; Li, Weishi; Zhou, Feifei; Zhang, Fengshan; Zhang, Li; Pan, Shengfa; Chen, Xin; Diao, Yinze; Xia, Tian
Abstract : Study Design: Retrospective study. Objective: The aim of this study was to evaluate the long-term clinical and radiographic outcomes of cervical arthroplasty using the ProDisc-C Vivo prosthesis. Summary of Background Data: Previous reports have shown that cervical arthroplasty with ProDisc-C artificial disc has acceptable clinical outcomes at 5-year and 10-year follow-ups. Methods: Clinical and radiographic evaluations, including dynamic flexion-extension lateral images, were performed at baseline and at the 5-year follow-up. Results: Twenty-eight patients who underwent single-level ProDisc-C Vivo arthroplasty were followed-up for a mean period of 65 months. The range of motion at the operated level was 8.9° ± 2.3° at baseline and 8.3° ± 4.8° at the final follow-up ( P   =  0.494). Fourteen of 28 levels (50%) developed heterotopic ossification (HO). According to McAfee's classification, one level was classified as grade I, nine levels as grade II, two levels as grade III, and two levels as grade IV. Only four of 28 levels (14.3%) had severe HO. Among patients with cervical spondylotic myelopathy, mJOA score was 13.9 ± 2.5° at baseline and 15.9°  ± 1.0° at the final follow-up ( P   =  0.001 < 0.05). Among patients with cervical spondylotic radiculopathy, Visual Analog Scale (VAS) neck and shoulder was 5.4 ± 1.4° at baseline and 0.7° ± 1.2° at the final follow-up (p = 0.000 < 0.05), VAS arm was 5.1 ± 2.8° at baseline and 0.5° ± 1.2° at the final follow-up ( P  =  0.000 < 0.05). A total of 49 adjacent segments were observed and 13 (26.5%) had adjacent segment degeneration. No patient developed recurrent cervical radiculopathy or myelopathy due to adjacent segment disease. No patient underwent re-operation. Conclusion: ProDisc-C Vivo arthroplasty had satisfactory clinical and radiographic outcomes at 5-year follow-up. Level of Evidence: 4 Abstract : This was the first long-term follow-up study evaluating the clinical and radiological outcomes of ProDisc-C Vivo, which was found to be a safe and effective treatment for single-level symptomatic cervical disc disease. The ROM was well preserved and HO rates were reduced.